A study on the relationship between pre-service English teachers’ self efficacy level and their classroom management beliefs / Ahmad Alief Esmail @ Ismail - Ahmad Alief, Esmail @ Ismail (2010)
This study examined the relationship between teacher efficacy and classroom management beliefs among pre-service teachers taking their Bachelors of Education (Honors) TESL in UiTM Kampus Bandaraya. These pre-service teachers have been sent to schools all over Melaka for their teaching practicum. The data is collected using an instrument adapted from Woolfolk & Hoy (1990) Teacher Efficacy Scale. Findings suggested that there is a strong positive correlation between the pre-service teachers’ self efficacy level and their classroom management beliefs. From the findings also it can be concluded that the program the pre-service teachers went through before their teaching practicum has prepared them well because their self efficacy level registered positive values. The major implication from this study is that pre-service teacher should be made aware of the importance of their self efficacy level how it can affect their classroom management beliefs and by creating this awareness, pre-service teachers with low self efficacy can be taught in order to increase their self efficacy level.